University extension and social outreach - Hidalgo Rosas, Gregorio Américo (2014)
University is one of the social actors, it not only has the roles of academic training and research, but also those of university extension and social outreach. This allows the interaction with the community to contribute to its development and to get enriching experiences. These essential objectives, clarified in University Law and Statute, are lagging behind in our Faculty of Education, since it lacks of an updated strategic plan, economical support and participation of all. Besides, this is a way to train the student for the world which is not taken into account in the study plan.